Immigrant Children in Canadian Schools: Factors Affecting Academic Performance Including Social Integration - Miners, Jhoanna (Université d'Ottawa | University of Ottawa, 2009)
Alarmingly, previous studies found the academic performance of immigrant and first generation children in Western societies are inferior to the academic performance of their non-immigrant counterparts. Often, this finding has been used as a causal argument to the lower educational attainment, employment and material/financial outcomes of this demographic in their adult years. If this set of propositions were true, then Canada faces and will continue to face serious public policy challenges because this demographic constitutes approximately 20% of all children in Canada. To explore this public policy scenario, this study aims to verify if children in Canada experiences this academic gap using OLS regression models from the first three cycles of Statistics Canada‟s* National Longitudinal Survey of Children and Youth (NLSCY). Contrary to other studies, the results show that all children in Canadian schools perform at similar academic levels. Some evidence was found, though limited, about the declining academic aptitude of immigrant children after attending and integrating in Canadian schools which suggests an opposite outcome to the predominant arguments and results found in existing literature. The paper also argues and finds that for the most part, academic difference are driven by the students‟ linguistic skills, their ability to get along with others, and participation in social activities, as well as their parents‟ attitudes towards education, and their family‟s socio-economic status (SES) rather than the students‟ country of birth or immigrant status.